PENDEKATAN DAN ANALISIS DALAM PENELITIAN TEKS TAFSIR: - Samsudin, Sahiron (SUHUF, 2019)
Observing the many of methodological problems in conducting research on the works of the Qur'an and its interpretations, the author of this article explains certain approaches and analyzes that have been used by some prominent researchers in this area. The author describes the possible approach which is divided into two main parts: (1) critical approach of history, and (2) an interpretative approach. The main objective of the first approach is to evaluate, to whom the text of a particular interpretation must be addressed to, and how to some extent the certain statements in the interpretation can be considered correct. The second approach can be done by doing three types of analysis: (1) descriptive analysis, (2) explanatory analysis, and (3) critical analysis. According to the author, the research in the field of Qur'an and its interpretation requires not only Islamic sciences, but also contemporary theories in the fields of sociology, literature, philosophy, hermeneutics, and feminism. The writer expects that researchers in the field of interpretation should take the opportunity to deepen these supporting sciences in order that the research will be more developed and varied.